2006
DOI: 10.1071/wr06025
|View full text |Cite
|
Sign up to set email alerts
|

Dietary analysis of regurgitates and stomach samples from free-living Australian sea lions

Abstract: Dietary remains recovered from Australian sea lion (Neophoca cinerea) digestive tracts and regurgitate samples from Seal Bay (Kangaroo Island, South Australia) were used to identify prey species consumed. Four of eight digestive tracts collected (50%) contained prey items located only in the stomach. On the basis of biomass reconstruction of cephalopod prey remains, octopus contributed 40% of the biomass in the samples, giant cuttlefish (Sepia apama) contributed 30% and ommastrephid squids contributed 14% biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 35 publications
1
43
1
Order By: Relevance
“…Limited dietary analysis of Australian sea lions suggests a broad range of prey from crustacean, teleost fish, elasmobranchs, and Little penguins Eudyptula minor spanning several trophic levels (Richardson & Gales 1987, Gales & Cheal 1992, McIntosh et al 2006. This is consistent with our findings of δ 15 N variation spanning almost 3 trophic levels.…”
Section: Individual Long-term Specialisation In Foraging Behavioursupporting
confidence: 82%
“…Limited dietary analysis of Australian sea lions suggests a broad range of prey from crustacean, teleost fish, elasmobranchs, and Little penguins Eudyptula minor spanning several trophic levels (Richardson & Gales 1987, Gales & Cheal 1992, McIntosh et al 2006. This is consistent with our findings of δ 15 N variation spanning almost 3 trophic levels.…”
Section: Individual Long-term Specialisation In Foraging Behavioursupporting
confidence: 82%
“…Captive Australian sea lions are fed fish with a limited range in terms of both species and size that have been processed through fish markets, while wild sea lions have a broad diet of primarily benthic prey, including octopus (Octopus spp. ), giant cuttlefish (Sepia apama), squid (Sepioteuthis australis), and southern rock lobster (Jasus edwardsii) from inshore to the shelf edge (McIntosh et al 2007;Gibbs et al 2011). The introduction of microbes from unnatural prey may be contributing to variations in microbial diversity in captivity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies observing the influence of diet on gut microbiota of fish and mammalian livestock species have shown that animals that forage manifest greater microbial diversity than those fed from artificial or concentrate sources (47)(48)(49). The varied diet of wild Australian sea lions includes a number of species with chitinous body parts, including small crustaceans, rock lobster, and cephalopods such as cuttlefish, octopus, and squid (27,28). This contrasts with the diet of captive animals, which are fed fresh or frozen fish almost entirely (28).…”
Section: Discussionmentioning
confidence: 99%
“…The varied diet of wild Australian sea lions includes a number of species with chitinous body parts, including small crustaceans, rock lobster, and cephalopods such as cuttlefish, octopus, and squid (27,28). This contrasts with the diet of captive animals, which are fed fresh or frozen fish almost entirely (28). Studies looking at the chitinolytic bacteria in the feces of wild herbivores (50), sheep (51), and humans (52) found that the majority of identified bacteria belonged to the genus Clostridium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation